Those Good Guys who Turn Bad and Stronger Have a Morphological Marker on Their Names? - Purnomo, SF. Luthfie Arguby; Gunawan, Fahmi; Kusciati, Karunia Purna; Untari, Lilik; Syafriza, Haydar Malik; Surya, Adjit Panji; Saputra, Mar'i Muhammad Bima (Soegijapranata Catholic University, 2022)
It has been a formula in films, comics, animations, and games to narrate a protagonist who turns into an antagonist to offer an alternate narrative to enjoy. This good-to-evil and weak-to-strong transformation is followed by changes in the names of the characters. We argue that the name changes are marked by what we called as umbralatives, an augmentative marker to indicate that a character has undergone a nuance shift from light to dark and an increase in power. This study attempts to address this phenomenon by proving the existence of umbralatives, their typology, and functions. Applying Zwicky and Pullum’s expressive morphology, Dressler and Barbaresi’s morphopragmatics, and Reinhart’s gestalt perception of narrative texts, we attempt to prove the existence of umbralatives. Implementing Spradleyan analysis on a corpus of characters from seventy one titles of animations, comics, films, and games, it was revealed that umbralatives are classified into colorative, stative, referentive, inventive, and elliptive. These five umbralatives function as a narrative marker in animations, comics, and films and a ludic marker in games. This study discloses a new field of study on morphology with special emphasis over the combination of morphopragmatics and onomastics – umbralatives. The results of the study might also disclose further investigations over good-to-evil narratives which we call umbral narratives.